Determinants of gap length in esophageal atresia with tracheoesophageal fistula and the impact of gap length on outcome - Muffazzal Rassiwala; Subhasis Roy Choudhury; Partap Singh Yadav; Praveen Jhanwar; Raghu Prakash Agarwal; Rajiv Chadha; Pinaki Ranjan Debnath (Wolters Kluwer Medknow Publications, 2016)
Aim: This study was aimed at identifying factors which may affect the gap length in cases of esophageal atresia with tracheoesophageal fistula (EA-TEF) and whether gap length plays any role in determining the outcome. Materials and Methods: All consecutive cases of EA-TEF were included and different patient parameters were recorded. Plain radiographs with a nasogastric tube in the upper esophagus were taken. Patients were grouped into T1-T2; T2-T3; T3-T4; and T4 depending on the thoracic vertebral level of the arrest of the tube. During surgery, the gap length between the pouches was measured using a Vernier caliper and the patients were grouped into A, B, and C (gap length >2.1 cm; >1-≤2 cm and ≤1 cm). The operative gap groups were compared with the radiography groups and the other recorded parameters. Results: Total numbers of cases were 69. Birth weight was found to be significantly lower in Group A (mean = 2.14 kg) as compared to Group B (mean = 2.38 kg) and Group C patients (mean = 2.49 kg) (P = 0.016). The radiographic groups compared favorably with the intraoperative gap length groups (P < 0.001). The need for postoperative ventilation (70.83% in Group A vs. 36.84% in Group C, P = 0.032) and mortality (62.5%, 26.9% and 15.8% in Group A, B, and C, respectively, P = 0.003) co-related significantly with the gap length. Conclusion: Birth weight had a direct reciprocal relationship with the gap length. Radiographic assessment correlated with intraoperative gap length. Higher gap length was associated with increased need for postoperative ventilation and poor outcome.